Analysis on Scientific and Technological Innovation of Grain Production in Henan Province Based on SD-GM Approach. (16th June 2022) - Zhang, Shuhua; Li, Bingjun; Yang, Yingjie; Zhang, Yifan
Abstract : A sustainable growth of grain outputs mainly relies on improving output per unit area through scientific and technological innovation. From the perspective of scientific and technological innovation, taking the grain production process as the research object, a systems model of scientific and technological innovation in grain production is constructed based on the relevant data of Henan Province from 2010 to 2019. Firstly, the internal mechanism of grain production scientific and technological innovation is explored, and the feedback loop of grain production scientific and technological innovation is then established. Secondly, system dynamics and grey system theory are combined to construct table functions and logistic functions to establish the grain production scientific and technological innovation system model. Through testing the model, the stability and feasibility of the model are demonstrated, and the simulation and prediction of the innovation system of grain production scientific and technological in Henan Province are carried out. Thirdly, in order to explore the impact of feasible policy schemes on grain production, seven policy plans are designed to simulate grain production policy scenarios from the perspective of scientific and technological innovation. The results show that: (1) The adjustment of individual policies, especially the adjustment of the protection policy of scientific and technological innovation in grain production or the subsidy policy of agricultural materials, has a weak influence on the improvement of grain output. The progress of agricultural technology is the main support for improving the comprehensive grain production capacity. (2) The future grain growth potential of Henan Province should focus on increasing the yield per unit area, and the protection of cultivated land resources should not be ignored. (3) The combination of policies has mutually reinforcing effect, which leads to an ideal system simulation effect. Finally, from the perspective of the composition of scientific and technological innovation system in Henan Province, this study puts forward countermeasures and suggestions for the implementation of the strategy of "storing grain in technology" in Henan Province.